Evaluation of Beauvericin’s activity and mode of action against all life stages of L. tropica for cutaneous Leishmaniasis therapy - Al Samra, Lynn; El Nahas, Mohamad; Mneimneh, Ilham; Sinno, Aia; Tokajian, Sima; Rahy, Kelven; Thoumi, Sergio; Ali, Lazo; Yammine, Wael; Al Khoury, Charbel (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundLeishmaniasis, particularly its cutaneous form caused by Leishmania tropica, remains a significant global health concern due to the limitations of current treatments, including drug resistance, toxicity, and inconsistent efficacy. This study investigates the potential of Beauvericin (BEA), a fungal secondary metabolite, as an alternative antileishmanial agent.ObjectivesThis study investigates the potential of Beauvericin (BEA), a fungal secondary metabolite, as an alternative antileishmanial agent.MethodsWe assessed the efficacy of BEA against different developmental stages of L. tropica using in vitro assays and an in vivo Galleria mellonella infection model. The ability of L. tropica to develop resistance to BEA and its effects on the parasite’s gene expression profile were also examined.ResultsBEA exhibited potent antileishmanial activity with equipotency across both promastigote and amastigote stages of L. tropica, with IC50 values of 0.25 µM and 0.27 µM, respectively, significantly lower than those of miltefosine. Mechanistically, BEA acts as a calcium ionophore, inducing a marked increase in intracellular calcium levels, which serves as the primary cytotoxic event. Transcriptomic profiling further revealed that BEA-induced calcium dysregulation triggers secondary cellular responses involving calcium homeostasis, lipid metabolism, and stress response, contributing to its multifaceted mechanism of action. The G. mellonella model demonstrated that BEA significantly reduced parasite burden, improved survival rates. Notably, BEA showed a slower rate of resistance development compared to ML, indicating its potential as a more sustainable treatment option.ConclusionsBEA is a promising candidate for antileishmanial therapy, demonstrating superior efficacy, a broad mechanism of action, and a favorable resistance profile compared to ML. Further investigations in mammalian models are warranted to validate BEA’s potential as a novel, cost-effective treatment for leishmaniasis.